ANALISIS SISTEM PENGENDALIAN MANAJEMEN RUMAH SAKIT YANG MENDUKUNG KINERJA INSTITUSI (STUDI KASUS DI RSUD BENDAN KOTA PEKALONGAN) - Jamaludin al J Efendi (JURNAL LITBANG KOTA PEKALONGAN, 2016)
THE PURPOSE OF THIS STUDY SPECIFICALLY TO TEST THE EFFECT OF MANAGEMENT CONTROL SYSTEM THAT INCLUDES A SYSTEM OF BELIEFS, BOUNDARY SYSTEM, DIAGNOSTIC CONTROL SYSTEM AND INTERACTIVE CONTROL SYSTEM ON THE PERFORMANCE OF HOSPITALS. POPULATION IN THIS STUDY WERE BENDAN HOSPITALPEKALONGAN CITY. A SAMPLE IS TAKEN WITH A PURPOSIVE SAMPLING METHOD A NUMBER OF 42 RESPONDENTS. THE RESEARCH METHODS USED IN THIS STUDY USING A QUANTITATIVE METHOD WITH MULTIPLE LINEAR REGRESSION USING SPSS VERSION 21 TO TEST THE HYPOTHESIS. THE RESULTS SHOWED THAT BELIEF'S SYSTEM, CONTROL SYSTEM DIAGNOSTICS AND INTERACTIVE CONTROL SYSTEM AFFECT THE FINANCIAL PERFORMANCE, THE LEVEL OF SIGNIFICANCE BELOW 0.05 WITH A VALUE OF T -3.164; -3.205; 2,754> T TABLE (2.024). WHILE THE SYSTEM BOUNDARY HAS NO DIRECT EFFECT ON THE FINANCIAL PERFORMANCE, THE SIGNIFICANCE LEVEL ABOVE 0.05 WITH A VALUE OF -0.184 T <T TABLE (2.024). TEST RESULTS ON THE PERFORMANCE OF EMPLOYEES INDICATE THAT THE BELIEF SYSTEM'S EFFECT ON THE PERFORMANCE OF THE EMPLOYEE, THE SIGNIFICANCE LEVEL BELOW 0.05 WITH A VALUE OF 2.487 T> T TABLE (2.024). MEANWHILE, THE SYSTEM BOUNDARY, CONTROL SYSTEM DIAGNOSTICS AND INTERACTIVE CONTROL SYSTEM DOES NOT DIRECTLY INFLUENCE THE PERFORMANCE OF THE EMPLOYEE, THE SIGNIFICANCE LEVEL ABOVE 0.05 WITH A VALUE OF 0,885 T; 0.063; 0.562 <T TABLE (2.024). FURTHERMORE'S BELIEF SYSTEM, THE SYSTEM BOUNDARY, CONTROL SYSTEM DIAGNOSTICS AND INTERACTIVE CONTROL SYSTEM JOINTLY SIGNIFICANT EFFECT ON THE PERFORMANCE OF HOSPITALS.